Power-Line-Triggered ESD Protection SCR for 0-20 GHz Applications in CMOS Technology - Chang, Chun-Rong; Lin, Chun-Yu (IEEE transactions on electron devices, 2023)
The high-speed circuits fabricated in the CMOS process are sensitive to the electrostatic discharge (ESD), so the ESD protection circuits are required in the chips. The protection circuit should not seriously impact the performance of high-speed circuits and provide wider bandwidth. In this work, a 0-20 GHz ESD protection design using a distributed structure with a novel power-line-triggered silicon-controlled rectifier (PLTSCR) is proposed. This protection circuit is demonstrated in a CMOS process, and the proposed design has been investigated to have area reduction and better ESD protection ability for high-speed applications.